- #1

chase222

- 12

- 1

tan x + cot x = (sec x)(csc x)

I changed the left side to:

tan x + 1/tan x = (sec x)(csc x)

then crossed out the tan:

1 = (sec x)(csc x), but I got stuck there.

The next one I had trouble with was:

tan^2 x - sin^2 x = (tan^2 x)(sin^2 x)

I saw the left side being a^2 - b^2, so I factored it into:

(tan x + sin x)(tan x - sin x) = (tan^2 x)(sin^2 x)

I then changed the tan into sin/cos:

((sin x/cos x) + sin x)) ((sin x/cos x) - sin x)) , but got stuck there.

Can you help me solve these proofs?